Associations between sleep trajectories up to 54 months and cognitive school readiness in 4 year old preschool children - Tham, Elaine Kwang Hsia; Xu, Hai-Yan; Fu, Xiuju; Goh, Rick Siow Mong; Gluckman, Peter D.; Chong, Yap-Seng; Yap, Fabian; Shek, Lynette Pei-Chi; Teoh, Oon Hoe; Gooley, Joshua; Goh, Daniel Yam-Thiam; Schneider, Nora; et al. (Frontiers in Psychology, 2023)
Purpose: This study explores the association between the duration and variation of infant sleep trajectories and subsequent cognitive school readiness at 48-50 months Methods: Participants were 288 multi-ethnic children, within the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort. Caregiver-reported total, night and day sleep durations were obtained at 3, 6, 9, 12, 18, 24 using the Brief Infant Sleep Questionnaire and 54 months using the Child Sleep Habits Questionnaire. Total, night and day sleep trajectories with varying durations (short, moderate, or long) and variability (consistent or variable; defined by standard errors) were identified. The cognitive school readiness test battery was administered when the children were between 48 to 50 months old. Both unadjusted adjusted analysis of variance models and adjusted analysis of covariance models (for confounders) were performed to assess associations between sleep trajectories and individual school readiness tests in the domains of language, numeracy, general cognition and memory. Results: In the unadjusted models, children with short variable total sleep trajectories had poorer performance on language tests compared to those with longer and more consistent trajectories. In both unadjusted and adjusted models, children with short variable night sleep trajectories had poorer numeracy knowledge compared to their counterparts with long consistent night sleep trajectories. There were no equivalent associations between sleep trajectories and school readiness performance for tests in the general cognition or memory domains. There were no significant findings for day sleep trajectories. Conclusion: Findings suggest that individual differences in longitudinal sleep duration patterns from as early as 3 months of age may be associated with language and numeracy aspects of school readiness at 48 to 50 months of age. This is important, as early school readiness, particularly the domains of language and mathematics, is a key predictor of subsequent academic achievement.